2023
DOI: 10.1111/ijn.13172
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare interventions for older people with dementia and family caregivers in Europe: A scoping review

Abstract: AimThis study aimed to examine the extent, range and variety of research in Europe describing healthcare interventions for older people with dementia (PwD) and family caregivers.MethodsThis was a scoping review and followed the PRISMA Scoping Review guideline. MEDLINE, CINAHL and Cochrane library databases were searched for studies published between 2010 and 2020. Studies reporting healthcare interventions in Europe for PwD over 65 years and their family caregivers were included.ResultsTwenty‐one studies from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Lord et al, 2020;Mahrer-Imhof et al, 2022;Mooney-Doyle et al, 2021). Despite providing evidence of the efficacy of family-focused interventions, the authors of these reviews identified considerable variation in the effects of interventions across families and limited attention to the family variables mediating and moderating intervention efficacy (García-Vivar et al, 2023). Reviewers also emphasized the need for theory-based interventions that are grounded in foundational research and informed by the underlying epistemological assumptions of the paradigm in which the research is situated.…”
mentioning
confidence: 99%
“…Lord et al, 2020;Mahrer-Imhof et al, 2022;Mooney-Doyle et al, 2021). Despite providing evidence of the efficacy of family-focused interventions, the authors of these reviews identified considerable variation in the effects of interventions across families and limited attention to the family variables mediating and moderating intervention efficacy (García-Vivar et al, 2023). Reviewers also emphasized the need for theory-based interventions that are grounded in foundational research and informed by the underlying epistemological assumptions of the paradigm in which the research is situated.…”
mentioning
confidence: 99%